Determination of the fracture pressure from CO2 injection time-series datasets. (June 2017) - Bohloli, Bahman; Ringrose, Philip; Grande, Lars; Nazarian, Bamshad
Highlights: Datasets of CO2 injection from In Salah and Snøhvit sites are presented. Three approaches are presented for determination of in-situ fracture pressure. Gap in injection rate (blank-rate) indicates transition from matrix to fracture flow. Plot of injection pressure vs rate in real time helps to ensure safe operation. Abstract: Successful operation of CO2 storage projects requires careful management of injection pressure to ensure that the integrity of the cap rock and other containment units is not compromised by mechanical failure. Injection of CO2 will lead to some increase in the pore pressure of the target storage formation and the project design will include some expected range of acceptable pressure variations required to achieve sufficient injectivity and to avoid loss of formation integrity. Accurate determination of the formation fracture pressures is a key factor controlling the maximum allowable injection pressure during operations. In this study we review the three main approaches for determining fracture pressure: (a) theoretical methods, (b) use of formation well-test data and (c) analysis of injection data during injection. While theoretical methods are valuable for early planning of projects, predictions based on formation well-test data are generally used immediately prior to and during injection operations. Using example site data, we show how careful analysis of wellhead pressure and rate data during injection operations may be used to optimize the injection plan using the actual in situ conditions in the rock formation around the injection well and for the specific properties of the injection fluid. Using injection pressure time-series datasets over an extended period of time allows improved accuracy in the estimation of the fracture pressure limits and an appreciation of their variation over a larger volume of the formation than can be estimated from well tests.